The Impact of Education in South Asia: Perspectives from Sri Lanka to Nepal - Namalefe, Susan Allen (Journal of International Students, 2020)
Education is produced within power relationships; therefore, power and social dynamics are central to any analysis of the impact of education. The acquisition and benefits of education are similarly intertwined by class, family, gender and social tensions, relentlessly mutating into different varieties, environments and appearances, and endlessly involving control. This is the essence of The Impact of Education in South Asia. Drawing from case studies, ethnographic research, and interviews from different parts of India, Nepal, and Sri Lanka, the authors attempt to provide perspective to the relationship between education and society. Formal education challenges society by changing gender roles, household organization, family, and the caste system. Individuals negotiate and transform culture and the educational system.